(untitled) (Anclajes, 2018)
The novel analyzed in the present work, El amante de Janis Joplin (2001) by Elmer Mendoza, recreates two simultaneous phenomena of recent Mexican history: the “dirty war” and the rise of drug trafficking. However, the sexual policies contained in the text are specific to the moment of enunciation, since they transgress the normative imperatives of both male and female heterosexuality, and in the first case they place the characters in a doubtful and infamous position related to homosexuality.